A scoping review of cognitive assessment tools and domains for chemotherapy-induced cognitive impairments in cancer survivors - Saita, Kazuya; Amano, Satoru; Kaneko, Fumiko; Okamura, Hitoshi (Frontiers in Human Neuroscience, 2023)
Backgrounds: Cancer survivors suffer from specific symptoms known as chemotherapy-induced cognitive impairments (CICIs). CICIs are difficult to capture with existing assessments such as the brief screening test for dementia. Although recommended neuropsychological tests (NPTs) exist, international consensus and shared cognitive domains of assessment tools are unknown. The aim of this scoping review was as follows: (1) to identify studies that assess CICIs in cancer survivors; (2) to identify shared cognitive assessment tools and domains by mapping the domains reported in studies using the International Classification of Functioning, Disability and Health (ICF) framework. Methods: The study followed the recommendations made by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. We searched the following three databases through October 2021: PubMed, CINAHL, and Web of Science. Prospective longitudinal or cross-sectional studies were selected to determine CICI-specific assessment tools for adult cancer survivors. Results: Sixty-four prospective studies (36 longitudinal studies and 28 cross-sectional studies) were included after checking for eligibility. The NPTs were divided into seven main cognitive domains. The specific mental functions were often used in the order of memory, attention, higher-level cognitive functions, and psychomotor functions. Perceptual functions were used less frequently. In some ICF domains, shared NPTs were not clearly identified. In some different domains, the same NPTs were used, such as the trail making test and the verbal fluency test. When the association between the publishing year and the amount of NPT use was examined, it was found that the amount of tool use tended to decline over the publication years. The Functional Assessment of Cancer Therapy-Cognitive function (FACT-Cog) was a shared consensus tool among the patient-reported outcomes (PROs). Conclusion: CICIs are currently gaining interest. Shared ICF domains such as memory and attention were identified for NPTs. There was a gap between the publicly recommended tools and the tools actually used in the studies. For PROs, a clearly shared tool, FACT-Cog, was identified. Mapping the domains reported in studies using the ICF can help in the process of reviewing consensus on which NPTs may be used to target cognitive domains.